ANALYSIS OF A GENETIC COLLECTION OF TOMATO CULTIVARS AND HYBRID FORMS FOR RESISTANCE TO LEAF MOLD USING DNA MARKERS - I. N. Shamshin; M. V. Maslova; Y. V. Gryazneva (Труды по прикладной ботанике, генетике и селекции)
Background. Leaf mold, a disease caused by the fungus Cladosporium fulvum Cooke in tomato, is one of the reasons for a significant decrease in the fruit yield. The most reliable and environmentally friendly way to protect tomato from diseases is the development of resistant cultivars and hybrids. The study of genetic aspects of disease resistance in plants is the basis of successful breeding work. Marker-assisted selection of the source forms of tomato is a relatively new approach in breeding, based on direct selection of plants for genes that determine the economically important traits. It allows for the time-saving analysis of breeding material.Materials and methods. The present work offers the results of screening more than 30 accessions from the genetic collection of tomato cultivars and hybrids of the Michurinsk State Agrarian University using the P7 molecular marker.Results and discussion. Polymorphism of the Cf-19 gene of resistance to leaf mold was evaluated, and clear reproducible results were obtained. To test the marker, seven hybrid forms of greenhouse tomato were used. The reliable identification of the Cf-19 gene by using the P7 marker was confirmed through artificial infection with C. fulvum. Six out of seven hybrids demonstrated a high level of resistance to the pathogen, which is confirmed by the originators’ data. A strong lesion was noted on the leaves of only one hybrid. The molecular genetic analysis has shown that among all control samples, only this genotype was a recessive homozygote. Besides, according to the originator, this genotype is not resistant to leaf mold. The performed test proves the high efficiency of the P7 marker. By using it, 35 genotypes were analyzed. The data obtained during the work show that the majority of the studied samples turned out to be heterozygous. At the same time, homozygous forms were also noted. For instance, the ‘Golden Rain’ tomato cultivar has only one 250 bp fragment, which corresponds to a recessive homozygote. Four genotypes were found to contain 300 bp fragments, which correspond to dominant homozygotes. The molecular genetic analysis revealed a number of genotypes that can be used as sources of resistance to leaf mold.